2014
DOI: 10.1007/s00421-014-2900-3
|View full text |Cite
|
Sign up to set email alerts
|

Selective muscle contraction during plantarflexion is incompatible with maximal voluntary torque assessment

Abstract: The results of this study suggest that using isolated contractions, hence constrained testing protocols, cannot provide optimal conditions for MVC testing, notably for plantarflexor muscles, which seem to be extremely sensitive to such constrained conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
2
4
1
Order By: Relevance
“…3 It has been shown that passing from supine to seated position greatly reduces plantarflexion torque development by modifying participation in torque production of muscles that do not span the ankle joint. 31 Moreover, this discrepancy can be explained by the fact that, despite subject familiarization with the experimental procedures, lower levels of voluntary activation at full knee extension were observed in our study, while previous studies have reported similar VA values between the 2 knee positions. 2,28 These results suggest that, under the methodological conditions of subject positioning (seated position without resting the trunk against the back of the chair) or of VA assessment (doublet superimposition in the present study vs. single superimposed twitch in previous studies), participants were not able to maximally activate the triceps surae at full knee extension despite a mechanical advantage of the 2 gastrocnemii at this position.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…3 It has been shown that passing from supine to seated position greatly reduces plantarflexion torque development by modifying participation in torque production of muscles that do not span the ankle joint. 31 Moreover, this discrepancy can be explained by the fact that, despite subject familiarization with the experimental procedures, lower levels of voluntary activation at full knee extension were observed in our study, while previous studies have reported similar VA values between the 2 knee positions. 2,28 These results suggest that, under the methodological conditions of subject positioning (seated position without resting the trunk against the back of the chair) or of VA assessment (doublet superimposition in the present study vs. single superimposed twitch in previous studies), participants were not able to maximally activate the triceps surae at full knee extension despite a mechanical advantage of the 2 gastrocnemii at this position.…”
Section: Discussioncontrasting
confidence: 86%
“…While some studies did not test full knee extension (160° and 170° respectively), in others subjects adopted a prone position for knee extension and a quadrupedal position for knee flexion . It has been shown that passing from supine to seated position greatly reduces plantar‐flexion torque development by modifying participation in torque production of muscles that do not span the ankle joint . Moreover, this discrepancy can be explained by the fact that, despite subject familiarization with the experimental procedures, lower levels of voluntary activation at full knee extension were observed in our study, while previous studies have reported similar VA values between the 2 knee positions .…”
Section: Discussionsupporting
confidence: 44%
“…The magnitude of T max/A obtained in a locked-unit mechanical configuration and with a 1D force sensor (100.5 ± 19.1 N m) was comparable with those of previous studies of young adults in the same ankle and knee positions (Hornsby et al 1987;Mademli et al 2004;Simoneau et al 2007;Turpin et al 2014). However, T max 1D/A values obtained with an open-unit mechanical configuration were significantly lower (P < 0.001) (~60 %) than those obtained with the classical locked-unit configuration.…”
Section: Discussionsupporting
confidence: 70%
“…6 They showed that maximal crank power was lower without handgrip on the handlebar (1136 ± 88 W) in comparison with handgrip (1461 ± 94 W), suggesting that the upper limb may influence the crank power. Nevertheless, hand gripping could influence the lower limbs' performance by inducing greater muscular activations, 7,8 suggesting that muscular/mechanical upper limbs' contribution to the crank power needs further verification.…”
mentioning
confidence: 99%